MODEL KOMPETENSI TENAGA KERJA INDONESIA BERDASARKAN ANALISIS KINERJA - Anita Kristina (Trunojoyo University of Madura, 2010)
This research aims to arrange the competency model using performance analysis. Descriptive qualitative and FGD methode is also used in this research. The result shows that the model arrange with performance analysis, there are mission, intension, background, purpose of the TKI. This analysis can be improved the cause of this problems, and the fund the conclution. The model shows that PJTKI needs the performance improvement in their management.